Protein structural dynamics at the gas/water interface examined by hydrogen exchange mass spectrometry. (2nd April 2015) - Xiao, Yiming; Konermann, Lars
Abstract Gas/water interfaces (such as air bubbles or foam) are detrimental to the stability of proteins, often causing aggregation. This represents a potential problem for industrial processes, for example, the production and handling of protein drugs. Proteins possess surfactant‐like properties, resulting in a high affinity for gas/water interfaces. The tendency of previously buried nonpolar residues to maximize contact with the gas phase can cause significant structural distortion. Most earlier studies in this area employed spectroscopic tools that could only provide limited information. Here we use hydrogen/deuterium exchange (HDX) mass spectrometry (MS) for probing the conformational dynamics of the model protein myoglobin (Mb) in the presence of N2 bubbles. HDX/MS relies on the principle that unfolded and/or highly dynamic regions undergo faster deuteration than tightly folded segments. In bubble‐free solution Mb displays EX2 behavior, reflecting the occurrence of short‐lived excursions to partially unfolded conformers. A dramatically different behavior is seen in the presence of N2 bubbles; EX2 dynamics still take place, but in addition the protein shows EX1 behavior. The latter results from interconversion of the native state with conformers that are globally unfolded and long‐lived. These unfolded species likely correspond to Mb that is adsorbed to the surface of gas bubbles. N2 sparging also induces aggregation. To explain the observed behavior we propose a simple model, that is, "semi‐unfolded" ↔ "native" ↔ "globally unfolded" → "aggregated". This model quantitatively reproduces the experimentally observed kinetics. To the best of our knowledge, the current study marks the first exploration of surface denaturation phenomena by HDX/MS.